Preparation, Characterization and Assessment of the Novel Gelatin–tamarind Gum/Carboxymethyl Tamarind Gum-Based Phase-Separated Films for Skin Tissue Engineering Applications. Issue 2 (22nd January 2017) - Shaw, Gauri Shankar; Biswal, Dibyajyoti; B, Anupriya; Banerjee, Indranil; Pramanik, Krishna; Anis, Arfat; Pal, Kunal
ABSTRACT: The current study delineates the development of novel gelatin–tamarind gum/carboxymethyl tamarind gum-based phase-separated films for probable skin tissue engineering applications. Polyethylene glycol was used as plasticizer. The films were characterized thoroughly using mechanical tester and impedance analyzer. Cell proliferation ability and drug release properties of the films were investigated. Mechanical studies indicated composition-dependent stress relaxation properties. Polysaccharide containing films supported better proliferation of human keratinocytes as compared to control. Drug-loaded films showed good antimicrobial properties against Escherichia coli . Analysis of the results indicated that the prepared films may be tried as matrices for skin tissue engineering. GRAPHICAL ABSTRACT: